GUT MICROBIAL DIVERSITY IN CARBOHYDRATE AND PROTEIN RICH DIET IN MALE FLIES OF Drosophila melanogaster - K., ANITHA; KRISHNA, M. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Objective: How the host organism and its gut bacteria interact to modulate host physiology. The goal of this study is to learn more about the impact of food composition on gut microbiota in D. melanogaster. Material and methods; Male flies of Drosophila melanogaster was raised in three different medium nomal diet (wheat cream agar medium), carbohydrate rich diet (20% of sucrose), protein rich diet (60% of casein). Twenty male flies midguts were isolated from each media and subjected to microbial diversity analysis. Result and conclusion; It was noticed in D. melanogaster that gutmicrobial vary with diet. The investigation revealed that gut microbial flora in relation to host diet corresponds to Acetobacters species and Lactobacillus species. A. pomorum, A. tropical, L. brevis, L. fructivorans, and L. plantarum. The relative abundance of each of the species varies in relation to host diet, Male flies of D. melanogaster fed on a carbohydrate-rich diet shows the highest density of L. plantarum and L. fructivorans bacteria. L. brevis, on the other hand, had the maximum density shown in male flies fed on protein-rich medium. Furthermore, males raised on a protein-rich diet shows the highest density of A. pomorum and A.tropicalis. Male flies raised on a normal diet had the lowest density of all five microbes from two distinct species. Thus these studies clearly explain that host physiology changes with diet, inturn, it has significant influence on resident gut microbial diversity in male flies of Drosophila melanogaster. As a result, our findings show that the diet of host has substantial impact on the density of gut microbial in D. melanogaster.